2019
DOI: 10.1021/acsami.9b11243
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Solid-Electrolyte Interface Facilitating Dendrite-Free Zinc Metal Anodes via Nanowetting Effect

Abstract: The formation of dendrites on a zinc (Zn) metal anode has limited its practical applications on aqueous batteries. Herein, an artificial composite protective layer consisting of nanosized metal–organic frameworks (MOFs) to improve the poor wetting effect of aqueous electrolytes on the Zn anode is proposed to reconstruct the Zn/electrolyte interface. In this layer, hydrophilic MOF nanoparticles serve as interconnecting electrolyte reservoirs enabling nanolevel wetting effect as well as regulating an electrolyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
178
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 251 publications
(193 citation statements)
references
References 33 publications
(46 reference statements)
3
178
0
Order By: Relevance
“…[21] To address the above issues,t he currently reported solutions can be divided into two aspects:s uppressing dendrite formation and minimizing side reactions.D endrite suppression can be achieved by introducing coating layers on Zn anode surface,which effectively modified the current and electrolyte flux on anode surface,s uch as CaCO 3 and SiO 2 layer, [22] porous active carbon layer and reduced graphene oxide (rGO) layer, [23,24] and so on. Furthermore,m any strategies have also been reported for relieving the side reactions beside suppressing dendrites,i ncluding coating az incophilic protective layer, [25] replacing ZnSO 4 with Zn-(CF 3 SO 3 ) 2 , [26] using electrolyte additives, [27][28][29] adoption of ah ighly concentrated zincic salt as electrolyte, [30] using modified conductive host, [31][32][33][34] employing single ion conduc-tive electrolyte, [35,36] alloying with Al, [37] adopting gel electrolyte or all solid electrolyte, [38][39][40] coating inorganic layer, [41][42][43][44] or organic (polyamide) layer. [45] Indeed, the side reactions and dendrite are very important issues for long life AZBs.…”
Section: Introductionmentioning
confidence: 99%
“…[21] To address the above issues,t he currently reported solutions can be divided into two aspects:s uppressing dendrite formation and minimizing side reactions.D endrite suppression can be achieved by introducing coating layers on Zn anode surface,which effectively modified the current and electrolyte flux on anode surface,s uch as CaCO 3 and SiO 2 layer, [22] porous active carbon layer and reduced graphene oxide (rGO) layer, [23,24] and so on. Furthermore,m any strategies have also been reported for relieving the side reactions beside suppressing dendrites,i ncluding coating az incophilic protective layer, [25] replacing ZnSO 4 with Zn-(CF 3 SO 3 ) 2 , [26] using electrolyte additives, [27][28][29] adoption of ah ighly concentrated zincic salt as electrolyte, [30] using modified conductive host, [31][32][33][34] employing single ion conduc-tive electrolyte, [35,36] alloying with Al, [37] adopting gel electrolyte or all solid electrolyte, [38][39][40] coating inorganic layer, [41][42][43][44] or organic (polyamide) layer. [45] Indeed, the side reactions and dendrite are very important issues for long life AZBs.…”
Section: Introductionmentioning
confidence: 99%
“…Based on Pourbaix diagram, free water in liquid neutral or mild acid electrolyte will unavoidably corrode the Zn metal anode and result in consecutive side reactions, which severely hinders the reversibility of ZMBs. [ 19 ] To tackle the issues mentioned above and improve the performance of Zn metal anodes, numerous strategies have been explored, including surface modification of Zn metal anodes, [ 20,21 ] anode structure design, [ 22,23 ] electrolyte composition optimization, [ 16,17,24–29 ] and using solid‐state electrolyte [ 30,31 ] and gel electrolyte. [ 32,33 ]…”
Section: Introductionmentioning
confidence: 99%
“…In the meantime, MOF particles impregnated with electrolyte can suppress the zinc dendrite formation due to the well‐contacted interfaces. [ 11 ] More recently, Zhou and co‐workers found that the microchannels of MOF (zeolitic imidazolate framework (ZIF)‐7) would reject large‐size solvated ion‐complexes and realize a super‐saturated electrolyte inside the channels under electric field. [ 36 ] As a result, the MOF‐coated zinc maintained ultralong lifespan of symmetric zinc half cells up to 3000 h at 0.5 mA cm −2 .…”
Section: Performance Optimization Of Zinc Anodesmentioning
confidence: 99%
“…AZIBs are composed by anodes, aqueous electrolyte, separators, and cathodes. [ 10 ] The cathodes are compounds which allow reversible insertion/extraction of Zn 2+ , such as manganese‐based material, [ 10 ] vanadium‐based material, [ 11 ] and Prussian blue derivatives. [ 12 ] .…”
Section: Introductionmentioning
confidence: 99%